Multinational Corporations and Local Firms in Emerging Economies - Rugraff, Eric; Hansen, Michael W.; de Haan, Ido; Cahen, Joel (EADI, 2011)
In order for foreign direct investment to have deep and lasting positive effects on host countries, it is essential that multinational corporations have close direct and indirect interaction with local firms. A valuable addition to the emerging literature on multinational-local firm interfaces, this book provides a number of case studies from emerging economies that examine such mutually beneficial business relationships and the policy measures necessary to support them.